TRANSFORMATION OF MILLENNIAL FARMERS: BETWEEN EXPECTATIONS AND REALITY - Wastutiningsih, Sri Peni; Partini, Partini; Nugroho, Novendra Cahyo; Fatonah, Siti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
As the guardian of food security as well as the pillar of national economy, the agricultural sector has gone through many changes thanks to digitalization. Millennial farmers are expected to have the ability to transform the agricultural system from conventional to contemporary agriculture that farmers should also be competent agripreneurs. This research aimed to examine the readiness of millennial farmers to cope with disruption as well as to analyze their regeneration in realizing agripreneurship for sustainable agricultural development. This research was conducted during August-December 2022 in Bantul and Klaten Regency by applying a critical constructivism approach to farmer informants, extension workers and other related stakeholders. Data was collected through observation, in-depth interviews and focus group discussions. The results indicated that: Becoming resilient millennial farmers in facing the digitalization of agricultural system was done by transforming technology and social media, as well as commodifying agricultural products from food crops to horticultural crops and even extending to the livestock subsector. Networking can also shape millennial farmers with competent agripreneurship. The choice to work in horticulture farming and livestock sub-sectors further strengthens the position of millennial farmers. Following this success can cause social transformation, which can also change the stigma, values, and mindset of the farmer's society. The existence of millennial farmer groups can be positioned as an image medium for the agricultural sector. Millennial farmers can be placed as an image to change the mindset of farmers towards the agricultural sector, and they can be a bridge for senior farmers to see market opportunities for agricultural products. And in the end, agriculture is seen as a business unit, not just a job to fulfill family food needs.